The Effectiveness of Clean and Healthy Living Behavior Implementation on the Prevention of Helminthiasis Using Audiovisual Methods among Sixth-Grade Students at SDN Perwira II Bekasi - Yulia Agustina; Ida Susanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Intestinal worms are one of the infectious diseases that remain a health problem among elementary school children, especially in environments with suboptimal sanitation and hygiene practices. This condition can affect children's health status, growth, and learning abilities, thus requiring preventive measures through effective and easy-to-understand health education. One preventive measure that can be taken is to provide health education on Clean and Healthy Living Behaviors (PHBS) through audiovisual media as a means of conveying information that is easily understood by elementary school students. According to the World Health Organization (WHO) in 2023, around 1.5 billion people worldwide are still infected with intestinal worms. In Indonesia, the prevalence of intestinal worms in children is still high, ranging from 30% to 90%, and is related to the low implementation of PHBS. This study aims to determine the effectiveness of implementing PHBS in preventing intestinal worms using audiovisual methods in sixth-grade students at SDN Perwira II Bekasi in 2025.This study employed a quantitative approach with a pre-test and post-test design without a control group involving 50 students (N = 50) using a total sampling technique. Data were analyzed using the Wilcoxon test.The mean knowledge score increased from 56.40 to 82.60, and the mean attitude score increased from 58.20 to 84.10. The Wilcoxon test results showed a p-value of 0.000 < 0.05, indicating a significant effect of PHBS implementation using audiovisual methods on the prevention of helminthiasis. The results showed that education on Clean and Healthy Living Behavior (PHBS) delivered through audiovisual media significantly improved students’ knowledge and attitudes. Before the intervention, students’ understanding and attitudes toward PHBS were not optimal; however, after the educational intervention, positive changes toward the adoption of clean and healthy living behaviors were observed. Audiovisual media proved effective because it presents information in a concrete, engaging, and easily understood manner for elementary school–aged students. These findings confirm that audiovisual-based PHBS education has the potential to support the prevention of helminthiasis in school environments.